Bina Vokalia Learning As Extracurricular Activities In The Integrated Early Chilhood Education (PAUD) Of Salatiga Children Center - Sejati, Irfanda Rizki (Universitas Negeri Semarang, 2020)
The process of learning in early childhood education and kindergarten is never apart from musical activities, although it is mostly just singing and dancing. Singing is one of the learning activities that is carried out daily from beginning of class to the end of class. Integrated PAUD Satya Wacana Children Center Salatiga provides a form of extracurricular Bina Vokalia at school to support learning, improve and develop student talent in singing. Vocal teaching of children is definitely different than adults, the delivery of the song material should be interesting to learners and in teaching the child's vocal techniques is need patience and technique. In view of today's modern times, many parents are increasingly giving their children activities outside school, especially music. Integrated PAUD Satya Wacana Children Center provides a vocal building learning facility that might develop a child's talent for music. The problem considered in the study is